Job Redesign as a Strategy to Reduce Burnout Among Nurses: A Theoretical Perspective - Moses Siruri Marwa; Jane Muthoni Kinuthia (European Scientific Journal, ESJ, 2025)
Burnout is a common phenomenon in many modern-day organizations. However, the literature shows that burnout is more pronounced in nurses than in other categories of healthcare workers.  Unfortunately, there is a dearth of scholarly studies on how organization development interventions can help reduce burnout among nurses. The aim of this study hence, was to examine how job redesigns can be employed as organization development intervention strategies towards the reduction of burnout among nurses. The methodology adopted was conceptual analysis of key job design theories, which include the Sociotechnical Systems Theory, the Job Characteristics Model, the Job Demands-Resources (JD-R) Model, and the Job Demand-Control Model. From the study, job enrichment and job crafting as job redesign interventions have been identified as promising interventions that can subsequently be explored as dimension-specific initiator variables in empirical studies for evidence-based policy guidance and decision making.